THE INFLUENCE OF EXCELLENT SERVICESAWARENESS TOWARD EMPLOYEE’S MOTIVATION IN SUPIORI LOCAL PUBLIC HOSPITAL - Feranianty Harpina; Djoko Wahyono; Edi Prasetyo Nugroho (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The overall good service system is by patient satisfaction-oriented system, besides the hospital facility aspects, the role of doctors, paramedical and non medical is very important as they will determine the perception of performance and perceived performance of the services provided patients. Asking a good service needs motivation supported by awareness on the importance of excellent service. The study was done in order to see the level of employee knowledge about the excellent service, looking at the relationship of employee knowledge level for the excellent service with the awareness level for excellent level, and to see how the influence of awareness of excellent service to the employee working motivation in Supiori Local Public Hospital. The subjects for this research consists of 37 permanent employee of Supiori Local Public Hospital, then analized using visual binning of SPSS 17 for windows program to see the employee knowledge level on the excellent service, the method of correlation analysis to see the correlation of employees knowledge level for the excellent service, and regression analysis method to see how the influence of awareness for excellent service by the employee to the Supiori Local Public Hospital using SPSS 17 for windows. The results showed that the respondents’ knowledge level classified as good one are 59.5% and 40.5% were considered not good. Knowledge of excellent service with awareness level for excellent service correlate with r-count of 0.692. The awareness effect of the excellent service to the working motivation by the employees in Supiori Local Public Hospital is 12.7% with the regression equation Y = 12.943 + 0.324 X.Keywords : Excellent service, work motivation